Cutaneous gnathostomiasis, first confirmed case in Colombia - Jurado, Leonardo F.; Palacios, Diana M.; López, Rocío; Baldión, Margarita; Matijasevic, Eugenio (Biomedica, 2015)
Gnathostomiasis is a parasitic zoonosis caused by some species of helminthes belonging to the genus Gnathostoma. It has a wide clinical presentation and its diagnosis is a challenge. Tropical and subtropical countries are endemic, and its transmission is associated with eating raw or undercooked meat from fresh water animals. Increasing global tourism and consuming exotic foods have produced a noticeable rise in cases of the disease in the last decades. However, in our country, there has not been any confirmed case of gnathostomiasis previously reported. We present the case of a 63-year-old Colombian man with an international travel history, who presented with gastrointestinal symptoms. During the hospital stay, he developed a cutaneous lesion on the upper right abdominal quadrant, where later, a larva was found. A morphological study allowed us to identify it as Gnathostoma spinigerum. As such, this is the first report of an imported case of gnathostomiasis confirmed in Colombia. This article describes the principles, etiology, pathogenic cycle and treatment of this disease with special considerations to our patient’s particular features.